The Focus and Target: Angiogenesis in Refractory Wound Healing. (December 2018) - Cheng, Biao; Fu, Xiaobing
In recent years, wound repair, especially chronic and refractory wounds, is still a growing worldwide health problem that concerns the physical and mental health of patients and the productivity of society as a whole. In many developed countries and developing countries, such as China, rapid economic growth, negative lifestyle changes (such as increased dietary fat intake and reduced physical activity), and increasingly serious aging problems have led to more and more refractory wounds caused by chronic diseases, such as diabetes and microvascular diseases. There is a clear and orderly stage in the process of wound healing, and the malfunction of any step will lead to poor healing effect. There are many causes of refractory wounds, among which the poor vascular network is closely related. This review focuses on the role and improvement of the microvasculature in wound repair. In addition, the future developmental trend of wound regenerative therapy (active factors, [stem] cells, tissue-induced biomaterials, gene therapy, etc) is also considered.